Propionibacterium acnes, Coagulase-Negative Staphylococcus, and the “Biofilm-like” Intervertebral Disc - Coscia, Michael F. (Spine (Phila Pa 1976), 2016)
STUDY DESIGN. Patients scheduled for spinal surgery were screened prospectively for a microbial presence associated with intervertebral disc specimens. Inclusion was limited to patients requiring surgery for any of five conditions: study patients with cervical spine intervertebral herniation (IVH), lumbar spine IVH, lumbar spine discogenic pain, and control patients with idiopathic scoliosis/Scheurermann's kyphosis or trauma/neuromuscular deformity. Exclusion criteria included ongoing systemic infection, abnormal pre-operative white cell counts, documented or suspected spinal infection, or previous surgery to the involved disc. OBJECTIVE. The aim of this study was to test for an association between the presence of a bacterial entity in operated discs and a diagnosis of pathologic disc disease. SUMMARY OF BACKGROUND DATA. An association has been described between microbial colonization and progressive intervertebral disc degeneration in 36 herniation patients undergoing microdiscectomies. A total of 19 patients had positive cultures on long-term incubation, with Propionibacterium acnes present in 84% of discs. MATERIALS AND METHODS. Discs were harvested during surgery, using strict sterile technique. Each disc was divided, with half the sample sealed in a sterile, commercially prepared anaerobic culture transport container, and half fixed in formalin. Live specimens were cultured for bacteria at a university-affiliated laboratory in a blinded fashion. Fixed pathologic specimens were gram-stained and read by a board-certified pathologist. RESULTS. A total of 169 intervertebral discs from 87 patients were evaluated (46 males, 41 females). Positive cultures were noted in 76 of 169 discs (45%), with 34 discs positive for P. acnes and 30 discs positive for Staphylococcus. No pathologic evidence was seen of microorganisms, acute or chronic inflammation, or infection. Pooling the IVH and discogenic pain patients and contrasting them with control patients showed a significant association of IVH with positive bacterial cultures (χ (2) = 15.37; P = 0.000088). CONCLUSION. Endemic bacterial biofilms are significantly associated with IVH and discogenic pain. Level of Evidence: N/A